The influence of rotating magnetic field on the welding arc motion status - Zhi-gang Li; Liang-ping Qiu; Ji-zhong Liu; Jian-xiong Ye; Di-qing Wan (Functional Materials, 2016)
A device generating rotating magnetic field is designed on the bas is of the mechanism of a rotating magnetic field. A rotating magnetic field and electric arc jointing together simulation is studied in this paper to elaborate arc characteristics and behavior under the action of a rotating magnetic field. The rotation radius of the arc are inversely proportional to the rotational frequency of the magnetic field. It is proportional to the field current. Due to constraint function of its own magnetic field of underwater wet welding arc. The influence on the underwater welding arc is smaller than the air welding arc while the magnetic field rotation frequency and magnetic field intensity is changed.